Determination of the drug utilization patterns of antimicrobial agents used in the department of ear, nose and throat at a tertiary care teaching hospital - Ingle, Satyashil A.; Divhare, Sujeet A.; Hiray, Rajesh S.; Shingare, Sujata (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Pharmacoepidemiology deals with the epidemiological aspects of clinical use of and effects of drugs over a large population with intentions to have a rationalised prescription practices while using various drugs preferably anti-microbial agents. Objective of the research was to study the prescribing patterns of drugs in ear, nose and throat (ENT) department and to evaluate prescriptions according to World Health Organization (WHO) drug use indicators. Methods: A cross sectional, observational study was conducted in the department of ENT. Data was collected from the prescriptions of patients in outpatient (OPD) and inpatient department (IPD) both. Results: Total number of 250 prescriptions were analysed in which 1038 drugs were prescribed, with average number of drugs prescribed per prescription were 3.6 and 4.6 drugs among OPD and IPD group respectively. Anti-histaminic class of drugs were most prescribed drugs in OPD while in IPD, all anti-microbial agents were most prescribed class of drugs. There was a statistically significant difference between drugs prescribed by generic and branded names. When compared statistically, it was found that 1%, 59% and 40% prescribed drugs in OPD were from desirable, essential and vital class respectively. While 3%, 62% and 36% of prescribed drugs in IPD were from desirable, essential and vital class respectively. Conclusions: It is vital to aware prescribers about the importance of rationalised prescribing and avoid polypharmacy. A need for the development of prescribing guidelines and educational initiatives to encourage the rational and appropriate use of drugs, in order to give the inputs to the prescribing doctors.